Perfil de beta talassemia heterozigota obtido a partir de análise data mining em banco de dados - Domingos, Ana L. B. [UNESP]; Granzotto, Lucas A. [UNESP]; Belini Junior, Edis; Oliveira, Thiago Y. K.; Domingos, Ana C. B. [UNESP]; Bonini-Domingos, Claudia R. [UNESP] (Associação Brasileira de Hematologia e Hemoterapia e daSociedade Brasileira de Transplante de Medula Óssea, 2010)
Variations in the phenotypic expression of heterozygous beta thalassemia reflect the formation of different populations. To better understand the profile of heterozygous beta-thalassemia of the Brazilian population, we aimed at establishing parameters to direct the diagnosis of carriers and calculate the frequency from information stored in an electronic database. Using a Data Mining tool, we evaluated information on 10,960 blood samples deposited in a relational database. Over the years, improved diagnostic technology has facilitated the elucidation of suspected beta thalassemia heterozygote cases with an average frequency of 3.5% of referred cases. We also found that the Brazilian beta thalassemia trait has classic increases of Hb A2 and Hb F (60%), mainly caused by mutations in beta zero thalassemia, especially in the southeast of the country.
The profile of beta thalassemia obtained by data mining analysis in a database
Keywords: Data mining; beta thalassemia trait; Bioinformatics; Genetic diversity